ANALISIS CUSTOMER PERSONA DAN KEBUTUHAN PENGGUNA UNTUK PAYMENT INTEGRATOR DI INDONESIA: SEBUAH PENDEKATAN DESIGN THINKING” - Jaka Arya Pradana; Ellya Zulaikha (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
Along with the exponential growth of Indonesia’s digital economy, the need for efficient and user-centered payment solutions has become increasingly crucial for business actors (merchants). This study aims to comprehensively map the landscape of merchant needs in Indonesia related to payment integrator services, a field that is often dominated by technology-driven approaches rather than user-centered ones. Using a qualitative approach adapted from the early stages of the Design Thinking methodology (Empathize and Define), this study conducted in-depth interviews with five business entities from diverse sectors, including Internet Service Providers (ISPs), property management, and banking. The results identify three fundamentally different customer personas based on their primary decision drivers: (1) Cost-Driven Users, who prioritize the lowest transaction fees (MDR); (2) Quality & Risk-Driven Users, who emphasize system reliability, security, and regulatory compliance; and (3) Liquidity-Driven Users, who are highly sensitive to fund disbursement speed (settlement). Further analysis reveals universal pain points such as high costs and slow settlement, as well as desired gains such as payment channel flexibility and trust in service providers. These findings provide a strategic foundation for financial technology product developers to design sharper and more relevant value propositions that align with actual market needs, moving beyond standard feature offerings and creating sustainable competitive advantages. Keywords: Customer Persona, User Needs, Payment Gateway, Financial Technology, Design Thinking, Case Study, B2B Marketing.